PEMAKAIAN EJAAN DALAM SKRIPSI MAHASISWA JURUSAN MIPA FKIP UNIVERSITAS TADULAKO - Muh. Asri B. (Multilingual, 2014)
Every student who will be finished their undergraduate study, must arrange the paper which contains a scientific steps about the result of experiment or phenomena in a certain discipline and in a certain system. The aim of this paper is to describe the application and its frequency in spelling system of the student of Science Major of Pedagogy Faculty of University of Tadulako. The method which is applied is descriptive. It has result that shows the high frequent of language mistakes in thepaper, spelling system in particularly. Those mistakes are (1) the application of the capital and italic font. (2) the application of prepositions di, ke, and dari, (3)the application of punctuation which is consists of (a) full stop , (b) period, (c) colon, (d) hyphen, (e) question mark, and (f) slash.